2021
DOI: 10.3390/genes12091446
|View full text |Cite
|
Sign up to set email alerts
|

p53 mRNA Metabolism Links with the DNA Damage Response

Abstract: Human cells are subjected to continuous challenges by different genotoxic stress attacks. DNA damage leads to erroneous mutations, which can alter the function of oncogenes or tumor suppressors, resulting in cancer development. To circumvent this, cells activate the DNA damage response (DDR), which mainly involves cell cycle regulation and DNA repair processes. The tumor suppressor p53 plays a pivotal role in the DDR by halting the cell cycle and facilitating the DNA repair processes. Various pathways and fact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 130 publications
1
10
0
Order By: Relevance
“…Nodes with a high degree, also known as hubs, are more likely to play an essential role (He and Zhang, 2006). In line with this, multiple review articles have described the key role of MDM2 in the p53-MDM2-signaling axis as part of the DDR (Nag et al, 2013;Haronikova et al, 2019;Gnanasundram et al, 2021;Okazaki, 2022). In addition, we found that MDM2 is targeted by 44 different miRNAs.…”
Section: Figuresupporting
confidence: 76%
“…Nodes with a high degree, also known as hubs, are more likely to play an essential role (He and Zhang, 2006). In line with this, multiple review articles have described the key role of MDM2 in the p53-MDM2-signaling axis as part of the DDR (Nag et al, 2013;Haronikova et al, 2019;Gnanasundram et al, 2021;Okazaki, 2022). In addition, we found that MDM2 is targeted by 44 different miRNAs.…”
Section: Figuresupporting
confidence: 76%
“…It was shown, that endothelial p53 prevents eNOS phosphorylation and impairs endothelium-dependent vasodilatation; its overexpression in Mdm2/Mdm4 deficient mice leads to impaired endothelial function [ 22 , 23 , 24 ]. Moreover, the p53 plays the important role in the DNA damage response by halting the cell cycle and facilitating the DNA damage repair [ 25 , 26 ]. On the other hand, MDM2 is a component of the TRIM28/KAP1-ERBB4-MDM2 complex which links growth factor and DNA damage response pathways [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…p53 plays an important role in maintaining cell homeostasis [ 1 , 2 , 3 ]. This protein is a transcription factor which regulates the expression of many genes, especially in stress conditions, under which the p53 level is elevated.…”
Section: Introductionmentioning
confidence: 99%
“…In a healthy cell, the p53 level is low due to its ubiquitination by Mdm2 and then its degradation. In response to stress conditions, p53 is phosphorylated to prevent the Mdm2–p53 interaction and the p53 level gets higher [ 1 , 2 , 3 ]. Besides the full-length p53, there are several isoforms of this protein in the cell whose expression results from the usage of various transcription promotors, alternative splicing and various translation initiation sites [ 4 , 5 , 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%